DO PUBLIC AND PRIVATE DEBT LEVELS AFFECT THE SIZE OF FISCAL MULTIPLIERS? - Chairul Adi (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
This paper investigates the effectiveness of fiscal policies – as measured by the impact and cumulative multipliers – and how they interact with public and private debt. Harnessing the moderated panel regression approach, based on the yearly data set of several economies during the period from 1996 to 2012, the analysis is focused on the impact of spending-and-revenue-based fiscal policies on economic growth and how these fiscal instruments interact with public and private indebtedness. The result of spending stimuli advocates the basic Keynesian theory. An increase in public expenditures contemporaneously generates a positive multiplier, of around 0.29 – 0.44 and around 0.45 – 0.58 during two years. Decomposing the expenditures into their elements, this paper documents a stronger impact from public investment than that from government purchases. On the other hand, the revenue stimuli seem to follow the Ricardian Equivalence Hypothesis (REH), arguing that current tax cuts are inconsequential. The impact and cumulative multipliers for this fiscal instrument have mixed results, ranging from -0.21 to 0.05 and -0.26 to 0.06, respectively. Moreover, no robust evidence is found to support the argument that government debt moderates the effectiveness of fiscal policies. The size of the multipliers for both spending and revenue policies remain constant with the level of public debt. On the other hand, private debt appears to show a statistically significant moderating effect on spending stimuli. Its impact on spending multipliers, however, is economically insignificant. The moderation effect of private debt on the revenue stimuli does not seem to exist. Finally, this paper documents that both public and private debt exhibit a negative and statistically significant estimation for economic output.